2018
DOI: 10.1007/s10620-018-5125-1
|View full text |Cite
|
Sign up to set email alerts
|

Rome IV Diagnostic Questionnaire Complements Patient Assessment of Gastrointestinal Symptoms for Patients with Gastroparesis Symptoms

Abstract: In this study, Gp patients were characterized using the PAGI-SYM and R4DQ. DGp had more severe retching and vomiting, while PSGp had more severe upper abdominal pain. PDS and CNVS were the most prevalent Rome IV diagnoses. The combination of PDS and CNVS was typically seen in patients with Gp. R4DQ can be helpful to characterize Gp patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…Patients with gastroparesis typically report a variety of gastrointestinal (GI) symptoms including nausea, vomiting, early satiety, post-prandial fullness, and abdominal pain [6]. The symptoms of Gp may be indistinguishable from functional dyspepsia and chronic nausea and vomiting syndrome without assessment of gastric emptying [6]. The causes of abdominal pain in Gp patients can be multifactorial with somatic, visceral and neuropathic components [9].…”
Section: Symptoms Of Gastroparesismentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with gastroparesis typically report a variety of gastrointestinal (GI) symptoms including nausea, vomiting, early satiety, post-prandial fullness, and abdominal pain [6]. The symptoms of Gp may be indistinguishable from functional dyspepsia and chronic nausea and vomiting syndrome without assessment of gastric emptying [6]. The causes of abdominal pain in Gp patients can be multifactorial with somatic, visceral and neuropathic components [9].…”
Section: Symptoms Of Gastroparesismentioning
confidence: 99%
“…The National Institute of Diabetes and Digestive and Kidney Diseases -Gastroparesis Consortium studies on patients with symptoms of Gp found a number of patients with symptoms of Gp but normal gastric emptying, termed chronic unexplained nausea and vomiting (CUNV) [60]. Over a third of patients with symptoms of Gp have normal total gastric emptying suggesting that factors, in addition to slow gastric emptying, also appear to be important in the pathogenesis of Gp symptoms [6]. Assessment of regional gastric retention and fundic accommodation during GES may provide additional information regarding the pathogenesis of dyspeptic symptoms.…”
Section: Role Of Gastric Emptying In Symptoms Of Gastroparesismentioning
confidence: 99%
See 3 more Smart Citations